Entrepreneurial impact sourcing: a conceptual framework of social and commercial institutional logics. (20th January 2017) - Khan, Shaji; Lacity, Mary; Carmel, Erran
Abstract: This article answers calls for better characterizations of impact sourcing given its potential to create social impacts in conjunction with global sourcing. It introduces a conceptual framework consisting of four dimensions drawn from entrepreneurship literature: primary mission, success criteria, resource mobilization and innovation approach – that characterize entrepreneurial impact sourcing service providers. These four dimensions are anchored across ideal types of social and commercial institutional logics to explicitly account for and capture the dual social and commercial value orientations of impact sourcing service providers as acknowledged in the literature. We evaluate the utility of this framework by using it to assess a US‐based business process outsourcing social enterprise that focuses on the underserved workforce of military veterans and spouses of military personnel. We found that this firm used social logic for both the firm's primary mission and the firm's resource mobilization; it used commercial logic for its success criteria, and it used both logics for its innovation. Our analysis of the case substantiates the applicability of the framework for capturing variation in how impact sourcing providers may selectively draw upon different logics across the four dimensions. © 2017 John Wiley & Sons Ltd